PROBLEMS OF RESPONSIBLE SELF-MEDICATION OF ALLERGY SYMPTOMS AND FARMACEUTICAL COUNSELING - V. A. Izrafilova; S. N. Egorova; G. Kh. Garifullina; T. A. Akhmetova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2021)
Cure of allergy symptoms reported by a patient with the help of non-prescription antiallergic drugs, is one of the important aspects of a responsible self-medication.The aim of the study is to assess the peculiarities of consumers' behavior as pharmacy visitors, when choosing non-prescription antiallergic drugs, and to identify potential problems of pharmaceutical counseling for allergy symptoms regarding the responsible self-medication.Materials and methods. Sociological survey in the form of a questionnaire; graphoanalytical and comparative analyses.Results. The profile of an over-the-counter antiallergic drugs buyer in the pharmacies of Kazan was assessed in the following way: it is a woman aged 18-44 of a middle level of income, having a family of 3-4 people, ready to spend from 101 to 500 rubles on the purchase of antiallergic drugs, buying anti-allergic drugs not for the first time. The main reasons to seek for treatment were skin rash, redness and itching, which had also been observed in the past. The allergic nature of the disease had already been confirmed by the doctor. For the average consumer of over-the-counter antiallergic drugs, the most important criteria for choosing a medicine were: efficiency, safety, the doctor's recommendations and price. The medicines were purchased for the visitors themselves or their children. The customers were satisfied with the choice of non-prescription antiallergic medicines available in the pharmacy. The visitors generally trusted the pharmacists' advice and recognized them as health professionals, but considered that the main goal was not only to provide a pharmaceutical care, but also to profit from the sale of the drugs. The following flaws of pharmaceutical counseling when dispensing non-prescription antiallergic drugs, were identified: an improper diagnosis by a pharmaceutical specialist, the lack of recommendations to consult a doctor, incomplete provision of information on the use, storage, and the possibility of interaction with other drugs and food.Conclusion. Misdiagnosis and incomplete provision of information by pharmaceutical specialists on antiallergic the drugs that are approved for the over-the-counter dispensing, require the implementation of a pharmaceutical consultation algorithm for the visitors contacting a pharmacy with allergy symptoms.